The Potential Role of Microbial Biostimulants in the Amelioration of Climate Change-Associated Abiotic Stresses on Crops - Fadiji, Ayomide Emmanuel; Babalola, Olubukola Oluranti; Santoyo, Gustavo; Perazzolli, Michele (Frontiers in Microbiology, 2022)
Crop plants are more often exposed to abiotic stresses in the current age of fast-evolving climate change. This includes exposure to extreme and unpredictable changes in climatic conditions, phytosanitary hazards, and cultivation conditions, which results in drastic losses in worldwide agricultural productions. Plants coexist with microbial symbionts, some of which play key roles in the ecosystem and plant processes. The application of microbial biostimulants, which take advantage of symbiotic relationships, is a long-term strategy for improving plant productivity and performance, even in the face of climate change-associated stresses. Beneficial filamentous fungi, yeasts and bacteria are examples of microbial biostimulants, which can boost the growth, yield, nutrition and stress tolerance in plants. This paper highlights recent information about the role of microbial biostimulants and their potential application in mitigating the abiotic stresses occurring on crop plants due to climate change. A critical evaluation for their efficient use under diverse climatic conditions is also made. Currently, accessible products generally improve cultural conditions, but their action mechanisms are mostly unknown, and their benefits are frequently inconsistent. Thus, further studies that could lead to the more precisely targeted products are discussed.